Going deeper than common sense – revision of the exam in the course Public Health and Nutrition based on peer teacher discussions and constructive alignment theory - Rish, Yara (Improving University Science Teaching and Learning, 2023)
As a teacher and examiner on the master’s degree course “Public Health and Nutrition” in 2010, I found that the format and content of the final oral exam made it difficult to test students’ knowledge and their ability to apply it adequately. The curricular exam questions appeared to me superficial and easy, and did not allow us to assess deep learning, despite the fact that the intended learning outcomes (ILOs) for the course (Appendix A) included competences at the highest levels of the SOLO taxonomy (Biggs & Tang 2007). In spring 2012, I was one of the persons responsible for the course and it gave me a chance to try and improve the exam.